Une inscription méconnue de Cos/Cosa dans la cité des Cadurques - Sabine Armani (Gallia)
The study proposes to revisit the first edition of an inscription (AE 2016, 1052), which remained confidential, except for its publication in local exhibition catalogues. The marble plaque is preserved in several pieces (which can be fitted together) and it is damaged on all sides, except for the bottom edge. In 2007, at the site of Cos (Cosa) about ten km from Montauban (in the Tarn-et-Garonne department), the object was discovered (though no further details are known about its discovery). The site is well-known to local archaeologists and scholars since the 17th c. The marble plaque presents four incomplete lines of the original text. An epigraphic analysis of the document has attempted to contextualize the text within what appears to be the dedication of an evergetic deed to the civitas of the Cadurci, where the discovery was made. The inscription presents high-quality workmanship, making use of both separation points and inclusions, and seems to date from the 1st c. AD. This study aims to pay attention to the archaeology of the site, as well as to the internal coherence of the text, thus offering a new interpretation of this object. The first edition emphasised localism in its restitutions, considering the last letters of the first line as the epigraphic attestation –hitherto unseen as Cossa– of the local toponym. This toponym was known only by virtue of the Peutinger’s Table, which spells it Cosa. On the contrary, this new study favours a classical reading of the text, based on a more traditional formulation. Thus, in the first line, the original attempt at restitution, based on the hypothetical mention of the inhabitants of Cosa as a uicus, should be discarded. The reconstruction used in the first edition remains unparalleled. The logical explanation of the verb in the third person singular (dat) in the last line is that the letters in the first line are remnants of the donor’s civil status –a suggestion that is both plausible and economical, all the more so, as the letters are entirely compatible with tria nomina, in the nominative. Therefore, what is presented here is a new mention of a citizen of the civitas of the Cadurci, of which only two representatives were known until now –making it all the more difficult to ascertain the identity of the person in question. The letters at the end of the line (COSS), however, belong to onomastic cycles well-known in the Celtic world. The two intermediate lines are the most problematic. On line 2, the mention of the ciuitas Cadurcorum calls for several types of interpretation, depending on the position of the text preserved in the dedication. It could be the reminder of a decision made by the city authorities, such as the ordo decurionum; but it could also be a formula –as already seen in the province (CIL XIII, 1376-1377, 1379)– signalling that the evergetic act applied to the whole city. However, one cannot rule out the possibility that this line –which logically follows on from the line mentioning the civil status of the donor– was devoted to indicating his curriculum in the civitas of the Cadurci. The beginning of the third line is enigmatic: while the identification of the first letter (a Q) is easy thanks to certain paleographical characteristics, one must be more cautious restoring the word. It may correspond to a quaestorship exercised by the donor, or, more likely, to a coordinating conjunction of the idemq(ue) or adque/atque type between a word that has disappeared (a first donation related to water activities or a local curatorship) and aquam, which has been preserved in extenso. The plaque has therefore retained the trace of at least one donation, that of a water conveyance. It is also unknown whether this conveyance had a name, as is sometimes the case (AE 1989, 521 = 1991, 1222). Finally, the fourth (and final) line preserves, as we saw above, the verb in the third person singular, referring to the evergetic act, presumably preceded by an expression emphasising the generosity of the donor. Nothing states that the rest of the line should be completed with an official formula of the type l(ocus) d(atus) d(ecreto) d(ecurionum). Indeed, a hole is located below, perhaps for mounting purposes, which might indicate that the engraving of the last line was centered in order to highlight it. The absence of a symmetrical hole in the upper part of the plate may most likely be explained by the fragmentary nature of the object. Thus, a missing first line, perhaps a votive dedication, cannot be totally excluded. This proposed re-interpretation of this marble plaque, based on an analysis of the logical layout of the text, enables us to definitively rule out any reference to a local toponym.